Core-shell quantum dot, preparation method thereof and display device
By using gradient heating and high-active selenium precursors in green light QLED devices, combined with the use of fatty amines and phosphine ligands, the problem of poor optical stability of core-shell quantum dots is solved, and the green light QLED device is significantly improved Working life.
Patent Information
- Application Number
- CN202410326563.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-21
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the T95@1000cd/m2 of green light QLED devices have a short working life and cannot be commercially produced. This is mainly due to the poor optical properties of core-shell quantum dots, and the low fluorescence quantum yield and poor stability. The problem.
During the preparation process of core-shell quantum dots, a high-active first selenium precursor is added simultaneously by using gradient heating method to promote the rearrangement of core-shell interface components and eliminate the interface defects caused by lattice mismatch. Then, the molar ratio of the first selenium precursor and the second selenium precursor is controlled to ensure uniform epitaxial growth of the shell. Meanwhile, fatty amine ligands and phosphine ligands are used as quantum dot surface ligands to inhibit electron and hole defects.
It achieves good quantum dot forming, few defects, and high optical properties stability, which significantly improves the working life of green light QLED devices.
Smart Images

Figure CN119432380A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of quantum dots, and specifically relates to a core-shell quantum dot and a preparation method and a display device thereof. Background Art
[0002] Quantum dots, also known as semiconductor nanocrystals, are a new type of semiconductor nanomaterial with a size of 1-10nm. Due to the quantum size effect and dielectric confinement effect, they have unique photoluminescence (PL) and electroluminescence (EL) properties. Compared with traditional organic fluorescent dyes, quantum dots have high quantum yield, high photochemical stability, not easy to photolyze, as well as wide excitation, narrow emission, high color purity, and the luminescent color can be adjusted by controlling the size of quantum dots. Excellent optical properties have broad application prospects in the field of display technology.
[0003] Currently, green QLED devices show the best performance at low brightness. 50 @100cd / m 2 The lifetime has reached the practical application requirements in the low-brightness commercial field. However, the device's T 95 @1000cd / m 2 The working life is short and cannot be commercialized. How to design quantum dots and build long-life green light QLED devices based on synthesized quantum dots is a difficult problem that needs to be solved in the QLED field.
[0004] Compared with single-component core quantum dots, core-shell structured quantum dots formed by coating the surface of core quantum dots with shell materials with larger energy band width have higher optical and chemical stability. To coat the surface of core quantum dots with shell materials, it is necessary to consider the lattice mismatch between the core material and the shell material. The smaller the lattice mismatch, the smaller the structural difference between the two materials, and the easier the epitaxial growth. In addition, during the epitaxial growth process, lattice mismatch will lead to lattice strain and the formation of defect states at the core-shell interface or in the shell, thereby reducing the fluorescence efficiency and stability of the quantum dots. For core materials with large lattice mismatch, such as CdZnSe and shell materials, such as ZnS, a transition layer, such as ZnSe, ZnSeS, etc., is usually coated between the core and the shell in the prior art.
[0005] In the prior art, the synthesis method of green light CdZnSe core-shell quantum dots is often to react a cadmium source, a zinc source and TOP-Se to form a nucleus, then add a zinc precursor and TOP-Se at high temperature to coat the ZnSe shell; then add a mixed solution of TOP-Se and TOP-S to coat the ZnSeS. However, TOP-Se has low activity, a low degree of alloying of the coated shell, and interface defects caused by the core-shell lattice mismatch, which in turn affects the luminescence efficiency of quantum dots; in addition, most of the prior art uses TOP as an anionic ligand on the surface of quantum dots, but ignores the electronic defects caused by uncoordinated cations on the surface of quantum dots. Therefore, the core-shell quantum dots obtained by the above method have poor stability of optical properties. Even after subsequent coating with a ZnS shell, there are problems of low fluorescence quantum yield and poor stability, resulting in a short working life of green light QLED devices.
[0006] In view of this, the present invention provides a green light CdZnSe core-shell quantum dot and a preparation method and a display device thereof. The quantum dots have good shape and few defects. The quantum dots are used as the light-emitting layer to prepare the device, which can effectively improve the device life. Summary of the invention
[0007] The object of the present invention is to provide a core-shell quantum dot and a preparation method and a display device thereof. The quantum dots have good shape and few defects. The quantum dots are used as light-emitting layers to prepare devices, which can effectively improve the device life.
[0008] The first aspect of the present invention provides a method for preparing core-shell quantum dots, the method comprising the steps of:
[0009] S1. providing a reaction system containing quantum dot nuclei;
[0010] S2. Gradually increase the temperature of the reaction system of step S1, and simultaneously add a first selenium precursor, and after the temperature stabilizes, add a zinc precursor and a second selenium precursor to grow a ZnSe shell layer around the quantum dot core, wherein the activity of the first selenium precursor is higher than that of the second selenium precursor, and the molar ratio of the first selenium precursor to the second selenium precursor is (1-3):2.
[0011] The present invention adopts gradient temperature increase when continuing to encapsulate ZnSe shell after nucleation is completed, and simultaneously adds a highly active first selenium precursor, which can promote the rearrangement of core-shell interface components and eliminate the interface defects caused by core-shell lattice mismatch to the maximum extent.
[0012] Since the activity of the first selenium precursor is higher than that of the second selenium precursor, the inventors found that adding an excessive amount of the first selenium precursor under high temperature conditions will lead to uneven growth of the quantum dot size. Therefore, after the high temperature is stabilized, the low-activity second selenium precursor is injected, which makes the quantum dot shell grow uniformly epitaxially and further eliminates the defects between the core and the shell.
[0013] As a preferred embodiment of the method for preparing the core-shell quantum dots, the method further comprises the steps of:
[0014] S3, preparing a ZnSeS shell layer covering the ZnSe shell layer;
[0015] S4, adding a first sulfur precursor to the reaction system of step S3 for reaction, cooling the temperature, and then adding a second sulfur precursor to grow a ZnS shell layer covering the ZnSeS shell layer, wherein the molar ratio of the first sulfur precursor to the second sulfur precursor is (10-15): (1-5).
[0016] Specifically, in step S3, the first selenium precursor and the second sulfur precursor are mixed and added dropwise into the reaction system after the reaction in step S2. Further, the first selenium precursor and the second sulfur precursor are mixed in a molar ratio of 1:1 and added dropwise at a speed of 5 ml / h.
[0017] As a preferred embodiment of the method for preparing the core-shell quantum dots, in step S2, the first selenium precursor is selected from one of octadecene-selenium and selenium powder-octadecene suspension, and the second selenium precursor is selected from at least one of diphenylphosphine selenium, triphenylphosphine selenium, tributylphosphine selenium and triamylphosphine selenium. By regulating the reactivity of the selenium precursor, the ZnSe shell can be uniformly epitaxially grown. Furthermore, by using precursors with different reactivity to control the amount of the first selenium precursor with higher activity, the inventors found that if only the first selenium precursor is used, the particle size of the quantum dots will be uneven, the half-peak width will be wide, and the color purity will be low.
[0018] Furthermore, the zinc precursor in step S2 is selected from zinc carboxylates with a carbon chain length of 8 to 22, such as at least one of zinc oleate, zinc oxalate, zinc acetate, zinc carbonate, zinc stearate, zinc undecylenate, and zinc tetradecanoate.
[0019] Furthermore, the zinc precursor and the second selenium precursor are added to the reaction system in a dropwise manner, the zinc precursor is added at a dropwise speed of 1-3 ml / min, and the second selenium precursor is added at a dropwise speed of 3-8 ml / h. By adding materials in a dropwise manner and controlling the dropwise speed, the reaction is more complete, ensuring that the ZnSe shell grows little by little, the transition of the shell is very slow, and the increase of the band gap energy is slower, that is, the lattice adaptability is better and more stable, and there are fewer defects between the core and shell.
[0020] Furthermore, the zinc precursor is added dropwise first, and then the second selenium precursor is added dropwise. The zinc precursor is added dropwise first to ensure that zinc is excessive in the reaction system, the reaction is sufficient, and the shell grows uniformly.
[0021] As a preferred solution of the above-mentioned method for preparing core-shell quantum dots, in step S2, the temperature is gradually increased by 30°C within 5-10 minutes. Specifically, when coating the ZnSe shell, the temperature is gradually increased from 280°C to 310°C within 5-10 minutes to ensure a more complete reaction at a specific temperature point, thereby achieving a better shell coating effect.
[0022] Furthermore, the reaction time of the reaction system in step S2 is 15-40 minutes. The inventors found that within this time, the reaction is sufficient and the shell growth effect is good.
[0023] As a preferred embodiment of the method for preparing core-shell quantum dots, in step S1, under the protection of an inert gas, a cadmium source and a zinc source are mixed and heated to a first temperature for reaction, then the temperature is raised to a second temperature, and a first selenium precursor is added for reaction to obtain a reaction system containing a CdZnSe core.
[0024] Furthermore, the first temperature is 110°C-150°C, and the reaction time is 10-30min; the second temperature is 280°C, and the second temperature is maintained for 10-30min. At the first temperature, the cadmium source and the zinc source form a cadmium precursor and a zinc precursor respectively, and when the temperature is raised to the second temperature, they react with the added first selenium precursor to form nuclei.
[0025] Furthermore, the speed of adding the first selenium precursor is 1 ml / s, and the reaction time of adding the first selenium precursor is 1-5 min. The first selenium precursor has high reactivity and needs to be added quickly in a very short time to react.
[0026] As a preferred embodiment of the method for preparing core-shell quantum dots, the reaction system containing CdZnSe cores further comprises aliphatic amine ligands, and the volume ratio of the aliphatic amine ligands to the second selenium precursor is (1-3) : 5. The aliphatic amine ligands serve as cationic ligands on the surface of quantum dots to suppress electronic defects.
[0027] Furthermore, the fatty amine ligand is selected from at least one of oleylamine, octylamine, octadecylamine and octadecylamine.
[0028] As a preferred embodiment of the above-mentioned method for preparing core-shell quantum dots, in step S4, the first sulfur precursor is selected from at least one of diphenylphosphine sulfide, triphenylphosphine sulfide, tributylphosphine sulfide, and tripentylphosphine sulfide, the second sulfur precursor is selected from octadecene-thiol, and the thiol is selected from at least one of isooctyl mercaptan, n-octyl mercaptan, and dodecanethiol.
[0029] Furthermore, the first sulfur precursor is added to the reaction system in a dropwise manner, and the dropwise addition speed of the first sulfur precursor is 5-15 ml / h. The present invention drops the first sulfur precursor at a speed of 5-15 ml / h to make the ZnS shell grow slowly and ensure uniform growth.
[0030] Furthermore, the present invention adds the second sulfur precursor after the first sulfur precursor is added and reacted for 10-30 minutes. The addition of the second sulfur precursor increases the thickness of the ZnS outer shell layer. The present invention uses different sulfur precursors to prepare the ZnS outer shell layer, which can effectively suppress the non-radiative Resonance energy transfer and Auger recombination, the resulting quantum dots have excellent stability.
[0031] As a preferred solution of the method for preparing core-shell quantum dots, in step S4, the temperature is lowered to 200-250° C., and then the second sulfur precursor is added. The second sulfur precursor is reacted at 200-250° C. to prevent the anisotropic growth of quantum dots, and also allows the second sulfur precursor to be fully decomposed, thereby achieving gradual and uniform growth of the ZnS shell layer.
[0032] Furthermore, after adding the second sulfur precursor and reacting for 5-15 minutes, the temperature is lowered to 20-25° C. (ie, room temperature).
[0033] The present invention uses two different sulfur precursors when preparing the ZnS shell layer, which are added at different temperatures. On the one hand, they participate in the shelling reaction to make the ZnS shell layer grow uniformly epitaxially; on the other hand, the first sulfur precursor contains a phosphine ligand, which serves as an anionic ligand on the surface of the quantum dot and can inhibit the hole defects on the surface of the quantum dot, thereby improving the stability of the quantum dot.
[0034] The fatty amine ligand and phosphine ligand used in the present invention are indispensable ligands for promoting the synthesis of high-quality quantum dots with perfect emission. They not only suppress the hole defects on the surface of the quantum dots, but also suppress the electron defects, making the electron-hole transport recombination more efficient, achieving the purpose of efficient device emission, and thus improving the working life of the green light QLED device.
[0035] The second aspect of the present invention provides a core-shell quantum dot, which is obtained by the above-mentioned preparation method.
[0036] A third aspect of the present invention provides a display device, comprising the core-shell quantum dots described above.
[0037] Compared with the prior art, the core-shell quantum dots and the preparation method thereof of the present invention have at least the following advantages:
[0038] 1. After the nucleation is completed, the present invention adopts a gradient temperature increase when encapsulating the ZnSe shell, and the temperature is gradually increased by 30°C in a short period of time (the temperature is gradually increased from 280°C to 310°C within 5-10 minutes). At the same time, a highly active first selenium precursor, such as an ODE-Se suspension, is added to promote the rearrangement of the core-shell interface components and minimize the interface defects caused by the core-shell lattice mismatch.
[0039] 2. The first selenium precursor, such as ODE-Se suspension, is too active. Adding too much at high temperature will lead to uneven growth of quantum dots. Therefore, after stabilization at high temperature, a second selenium precursor with low activity, such as TBP-Se, is injected. This allows the quantum dot shell to grow uniformly and further eliminate defects between the core and shell.
[0040] 3. The present invention adds fatty amine ligands to the CdZnSe nucleation reaction system as cationic ligands on the surface of quantum dots to suppress electronic defects. At the same time, a first selenium precursor and a first sulfur precursor containing phosphine ligands are used, and the phosphine ligands are used as anionic ligands on the surface of quantum dots to suppress hole defects on the surface of quantum dots. Fatty amine ligands and phosphine ligands are indispensable ligands for synthesizing high-quality quantum dots with perfect emission, so that the optical properties of the synthesized CdZnSe core-shell quantum dots have higher stability, thereby improving the working life of the green light QLED device. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Attached Figure 1 The EQE data of QLED-1 device and QLED-2 device varies with brightness;
[0043] Attached Figure 2 This is the life test data chart of QLED-1 devices and QLED-2 devices. DETAILED DESCRIPTION
[0044] The following examples are described to assist the understanding of the present invention, and the examples are not and should not be interpreted in any way as limiting the scope of protection of the present invention.
[0045] As stated herein, for example, "at least one (individual)" modifies the entire list of elements when preceding or following a list of elements without modifying the individual elements of the list. If not otherwise defined, all terms (including technical and scientific terms) in the specification may be defined as those skilled in the art generally understand. The terms defined in the commonly used dictionaries should be interpreted as being consistent with their meanings in the context of the relevant art and the present disclosure, and may not be interpreted in an ideal manner or too broadly unless clearly defined. In addition, unless explicitly described to the contrary, the wording "including" and the wording "comprising" when used in this specification indicate the presence of the stated features, regions, wholes, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or their collections. Therefore, the above wording will be understood to mean including the stated elements, but not excluding any other elements.
[0046] As described in the background technology, the green light CdZnSe core-shell quantum dots prepared by the prior art have defects between the core and shell and between the surfaces, resulting in a short working life of the green light QLED device. The present invention provides a core-shell quantum dot and a preparation method and a display device thereof. The quantum dots have good shape and few defects. The quantum dots are used as the light-emitting layer to prepare the device, which can effectively improve the device life.
[0047] The first aspect of the present invention provides a method for preparing core-shell quantum dots, the method comprising the steps of:
[0048] S1. providing a reaction system containing quantum dot nuclei;
[0049] S2. Gradually increase the temperature of the reaction system of step S1, and simultaneously add a first selenium precursor, and after the temperature stabilizes, add a zinc precursor and a second selenium precursor to grow a ZnSe shell layer around the quantum dot core, wherein the activity of the first selenium precursor is higher than that of the second selenium precursor, and the molar ratio of the first selenium precursor to the second selenium precursor is (1-3):2.
[0050] The present invention adopts gradient temperature increase when continuing to encapsulate ZnSe shell after nucleation is completed, and simultaneously adds a highly active first selenium precursor, which can promote the rearrangement of core-shell interface components and eliminate the interface defects caused by core-shell lattice mismatch to the maximum extent.
[0051] Since the activity of the first selenium precursor is higher than that of the second selenium precursor, the inventors found that adding an excessive amount of the first selenium precursor under high temperature conditions will lead to uneven growth of the quantum dot size. Therefore, after the high temperature is stabilized, the low-activity second selenium precursor is injected, which makes the quantum dot shell grow uniformly epitaxially and further eliminates the defects between the core and the shell.
[0052] In some embodiments, the preparation method further comprises the steps of:
[0053] S3, preparing a ZnSeS shell layer covering the ZnSe shell layer;
[0054] S4, adding a first sulfur precursor to the reaction system of step S3 for reaction, cooling the temperature, and then adding a second sulfur precursor to grow a ZnS shell layer covering the ZnSeS shell layer, wherein the molar ratio of the first sulfur precursor to the second sulfur precursor is (10-15): (1-5).
[0055] Specifically, in step S3, the first selenium precursor and the second sulfur precursor are mixed and added dropwise into the reaction system after the reaction in step S2. Further, the first selenium precursor and the second sulfur precursor are mixed in a molar ratio of 1:1 and added dropwise at a speed of 5 ml / h.
[0056] In some embodiments, in step S2, the first selenium precursor is selected from one of octadecene-selenium and selenium powder-octadecene suspension, and the second selenium precursor is selected from at least one of diphenylphosphine selenium, triphenylphosphine selenium, tributylphosphine selenium and tripentylphosphine selenium. By regulating the reactivity of the selenium precursor, the ZnSe shell can be uniformly epitaxially grown. In addition, by using precursors with different reactivity to control the amount of the first selenium precursor with higher activity, the inventors found that if only the first selenium precursor is used, the particle size of the quantum dots will be uneven, the half-peak width will be wide, and the color purity will be low.
[0057] Furthermore, the zinc precursor in step S2 is selected from zinc carboxylates with a carbon chain length of 8 to 22, such as at least one of zinc oleate, zinc oxalate, zinc acetate, zinc carbonate, zinc stearate, zinc undecylenate, and zinc tetradecanoate.
[0058] Furthermore, the zinc precursor and the second selenium precursor are added to the reaction system in a dropwise manner, the zinc precursor is added at a dropwise speed of 1-3 ml / min, and the second selenium precursor is added at a dropwise speed of 3-8 ml / h. By adding materials in a dropwise manner and controlling the dropwise speed, the reaction is more complete, ensuring that the ZnSe shell grows little by little, the transition of the shell is very slow, and the increase of the band gap energy is slower, that is, the lattice adaptability is better and more stable, and there are fewer defects between the core and shell.
[0059] Furthermore, the zinc precursor is added dropwise first, and then the second selenium precursor is added dropwise. The zinc precursor is added dropwise first to ensure that zinc is excessive in the reaction system, the reaction is sufficient, and the shell grows uniformly.
[0060] In some embodiments, in step S2, the temperature is gradually increased by 30°C within 5-10 minutes. Specifically, when coating the ZnSe shell, the temperature is gradually increased from 280°C to 310°C within 5-10 minutes to ensure that the reaction at a specific temperature point is more sufficient, thereby achieving a better shell coating effect. First, the present invention first heats up to 300°C, and when the temperature quickly reaches 300°C, it slowly heats up to 310°C.
[0061] Furthermore, the reaction time of the reaction system in step S2 is 15-40 minutes. The inventors found that within this time, the reaction is sufficient and the shell growth effect is good.
[0062] In some embodiments, in step S1, under the protection of an inert gas, a cadmium source and a zinc source are mixed and heated to a first temperature for reaction, the temperature is raised to a second temperature, and a first selenium precursor is added for reaction to obtain a reaction system containing CdZnSe cores.
[0063] Furthermore, the first temperature is 110°C-150°C, and the reaction time is 10-30min; the second temperature is 280°C, and the second temperature is maintained for 10-30min. At the first temperature, the cadmium source and the zinc source form a cadmium precursor and a zinc precursor respectively, and when the temperature is raised to the second temperature, they react with the added first selenium precursor to form nuclei.
[0064] Furthermore, the speed of adding the first selenium precursor is 1 ml / s, and the reaction time of adding the first selenium precursor is 1-5 min. The first selenium precursor has high reactivity and needs to be added quickly in a very short time to react.
[0065] In some embodiments, the reaction system containing CdZnSe cores further comprises aliphatic amine ligands, and the volume ratio of the aliphatic amine ligands to the second selenium precursor is (1-3) : 5. The aliphatic amine ligands serve as cationic ligands on the surface of quantum dots to suppress electronic defects.
[0066] Furthermore, the fatty amine ligand is selected from at least one of oleylamine, octylamine, octadecylamine and octadecylamine.
[0067] As a preferred embodiment of the above-mentioned method for preparing core-shell quantum dots, in step S4, the first sulfur precursor is selected from at least one of diphenylphosphine sulfide, triphenylphosphine sulfide, tributylphosphine sulfide, and tripentylphosphine sulfide, the second sulfur precursor is selected from octadecene-thiol, and the thiol is selected from at least one of isooctyl mercaptan, n-octyl mercaptan, and dodecanethiol.
[0068] Furthermore, the first sulfur precursor is added to the reaction system in a dropwise manner, and the dropwise addition speed of the first sulfur precursor is 5-15 ml / h. The present invention drops the first sulfur precursor at a speed of 5-15 ml / h to make the ZnS shell grow slowly and ensure uniform growth.
[0069] Furthermore, the present invention adds the second sulfur precursor after the first sulfur precursor is added and reacted for 10-30 minutes. The addition of the second sulfur precursor increases the thickness of the ZnS outer shell layer. The present invention uses different sulfur precursors to prepare the ZnS outer shell layer, which can effectively suppress the non-radiative Resonance energy transfer and Auger recombination, the resulting quantum dots have excellent stability.
[0070] In some embodiments, in step S4, the temperature is lowered to 200-250° C. before adding the second sulfur precursor. Allowing the second sulfur precursor to react at 200-250° C. can prevent anisotropic growth of quantum dots and also allow the second sulfur precursor to be fully decomposed, thereby achieving gradual and uniform growth of the ZnS shell layer.
[0071] Furthermore, after adding the second sulfur precursor and reacting for 5-15 minutes, the temperature is lowered to 20-25° C. (ie, room temperature).
[0072] Those skilled in the art know that quantum dot surface ligand is one of the important factors determining its stability. Conventionally used alkyl phosphine compounds (R3P), alkyl phosphine oxides (R3PO) etc. belong to L-type ligands, and L-type ligands are prone to desorption during quantum dot purification, and the heat energy generated by device preparation and operation process can cause QD film material aging damage, greatly reducing the working life of the device. And the alkyl mercaptan (RSH) etc. used in the present invention belong to X-type ligands, and X-type ligands can form covalent bonds with quantum dot surface cations, and the sulfur atom at the end of the mercaptan can be embedded in the outer shell as a sulfur source, further strengthening the bonding, and this strong bonding enhances the light stability and thermal stability of quantum dots. At the same time, ligand replacement is carried out with short-chain alkyl ligands (thiol) and surface long-chain ligands (such as oleic acid), improving the surface passivation effect of quantum dots, and enhancing the electron mobility in the QD film.
[0073] The present invention uses two different sulfur precursors when preparing the ZnS shell layer because:
[0074] 1) Only TBP-S (tributylphosphine-sulfur) was used as the S source, and the TBP ligand was desorbed during purification and subsequent storage, causing quantum dots to agglomerate;
[0075] 2) If only IOT (isooctyl mercaptan) is used, IOT has a high reactivity and can participate in the reaction at 220°C. It reacts quickly at high temperatures and it is difficult to control the thickness of the ZnS shell;
[0076] 3) Combined reaction: TBP-S acts as the main S source to promote the stable coating of the ZnS shell. IOT acts as both a small S source and a surface short-chain ligand to improve the surface passivation effect, enhance the electron mobility in the QD film, improve the thermal stability of quantum dots, and increase the device working life.
[0077] The present invention uses two different sulfur precursors when preparing the ZnS shell layer, which are added at different temperatures. On the one hand, they participate in the shelling reaction to make the ZnS shell layer grow uniformly epitaxially; on the other hand, the first sulfur precursor contains a phosphine ligand, which serves as an anionic ligand on the surface of the quantum dot and can inhibit the hole defects on the surface of the quantum dot, thereby improving the stability of the quantum dot.
[0078] The fatty amine ligand and phosphine ligand used in the present invention are indispensable ligands for promoting the synthesis of high-quality quantum dots with perfect emission. They not only suppress the hole defects on the surface of the quantum dots, but also suppress the electron defects, making the electron-hole transport recombination more efficient, achieving the purpose of efficient device emission, and thus improving the working life of the green light QLED device.
[0079] The second aspect of the present invention provides a core-shell quantum dot, which is obtained by the above-mentioned preparation method.
[0080] According to a third aspect of the present invention, a display device is provided, comprising the core-shell quantum dots described above.
[0081] Display devices include: display devices, light emitting diodes (LEDs), organic light emitting diodes (OLEDs), quantum dot LEDs, quantum dot films, sensors, solar cells, image sensors, or liquid crystal displays (LCDs). Display devices include: electronic paper, mobile phones, tablet computers, televisions, monitors, laptop computers, digital photo frames, navigation systems, car displays, AR displays, and VR displays.
[0082] In addition to the core-shell quantum dot film, the display device may also include structures known to those skilled in the art in the technical field of the present invention. That is, the present invention includes a display device to which the core-shell quantum dot film of the present invention can be applied.
[0083] The present invention will be further described in detail below in conjunction with specific embodiments and comparative examples, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to different requirements of specific use, and the unspecified conditions are conventional conditions in the industry.
[0084] The first selenium precursor, the second selenium precursor, the first sulfur precursor, the second sulfur precursor, and the zinc precursor used in the examples are prepared in advance.
[0085] Preparation of the first selenium precursor (ODE-Se suspension):
[0086] 2 mmol of selenium powder was weighed into a conical flask, and 10 ml of ODE (octadecene) was added, and ultrasonic oscillation was performed to obtain a first selenium precursor ODE-Se suspension with a selenium concentration of 0.2 mmol / ml.
[0087] Preparation of the second selenium precursor (TBP-Se solution):
[0088] 4 mmol of selenium powder was weighed into a conical flask, and 10 ml of tributylphosphine was added, and ultrasonic oscillation was performed to obtain a second selenium precursor TBP-Se solution with a selenium concentration of 0.4 mmol / ml.
[0089] Preparation of the first sulfur precursor (TBP-S solution):
[0090] 4 mmol of sulfur powder was weighed into a conical flask, and 10 ml of tributylphosphine was added, and ultrasonic oscillation was performed to obtain a first sulfur precursor TBP-S solution with a sulfur concentration of 0.4 mmol / ml.
[0091] Preparation of the second sulfur precursor (IOT-ODE solution):
[0092] 1 ml of IOT (isooctyl mercaptan) and 5 ml of ODE (octadecene) were measured and mixed thoroughly to obtain a second sulfur precursor IOT-ODE solution.
[0093] Preparation of zinc precursor solution (zinc oleate):
[0094] Weigh 12 mmol of zinc oxide and place it in a three-necked flask, add 12 ml of oleic acid and 18 ml of octadecene, raise the temperature to 120°C, evacuate for 40 minutes, introduce nitrogen, raise the temperature to 280°C until the solution is clear, and cool to 120°C to obtain a zinc oleate solution with a cation concentration of 0.4 mmol / ml.
[0095] Embodiment 1:
[0096] 0.25mmol cadmium oxide, 2.5mmol zinc acetate, 1.5mL oleic acid, 0.5mL oleylamine and 5mL 1-octadecene were placed in a 100mL three-necked flask, vacuumed and heated to 120℃ with magnetic stirring for 20min. When the solution became transparent, it was heated to 280℃ under nitrogen protection and kept warm for 20min. Then, 1mL ODE-Se was quickly injected into the solution and reacted for 5min to obtain a CdZnSe core solution.
[0097] The solution temperature was gradually increased to 310°C within 10 min, during which 3 mL of LOD-Se was injected. After the temperature reached 310°C, 4 mL of zinc oleate solution was added dropwise to the reaction solution within 2 min, and 1 mL of TBP-Se was added dropwise to the reaction solution at a rate of 5 mL / h using an injection pump. The solution was kept at 310°C for 20 min to ensure the growth of the ZnSe shell.
[0098] A syringe pump was used to dropwise add 1 ml of TBP-Se and 1 ml of TBP-S mixture into the reaction solution at 5 ml / h, and the mixture was kept warm for 20 min to obtain a ZnSeS shell layer.
[0099] 3 ml of TBP-S was added dropwise into the reaction solution at a rate of 10 ml / h by a syringe pump, and the temperature was kept for 20 min. The reaction solution was cooled to 240°C, 0.5 ml of IOT-ODE solution was added, and the temperature was kept for 10 min. The temperature was cooled to room temperature to obtain a ZnS shell.
[0100] The quantum dots obtained in this example are recorded as QDs-1.
[0101] Comparative Example 1:
[0102] 0.25mmol cadmium oxide, 2.5mmol zinc acetate, 1.5mL oleic acid, 0.5mL oleylamine and 5mL 1-octadecene were placed in a 100mL three-necked flask, vacuumed and heated to 120℃ with magnetic stirring for 20min. When the solution became transparent, it was heated to 280℃ under nitrogen protection and kept warm for 20min. Then, 1mL ODE-Se was quickly injected into the solution and reacted for 5min to obtain CdZnSe core solution.
[0103] The solution temperature was quickly raised to 310°C, and 4 ml of zinc oleate solution was added dropwise to the reaction solution within 2 minutes. At the same time, 2.5 ml of TBP-Se was added dropwise to the reaction solution at 6 ml / h by a syringe pump. After the addition was completed, the temperature was kept at 310°C for 20 minutes to ensure the growth of the ZnSe shell.
[0104] A syringe pump was used to dropwise add 1 ml of TBP-Se and 1 ml of TBP-S mixture into the reaction solution at 5 ml / h, and the mixture was kept warm for 20 min to obtain a ZnSeS shell layer.
[0105] 3 ml of TBP-S was added dropwise into the reaction solution at a rate of 10 ml / h by a syringe pump, and the temperature was kept for 20 min. The reaction solution was cooled to 240°C, 0.5 ml of IOT-ODE solution was added, and the temperature was kept for 10 min. The temperature was cooled to room temperature to obtain a ZnS shell.
[0106] The quantum dots obtained in this comparative example were recorded as QDs-2.
[0107] In order to explore the stability of QLED devices constructed based on two types of quantum dots, devices were constructed based on QDs-1 and QDs-2, and life tests were carried out at the same time.
[0108] Preparation of QLED devices:
[0109] Step 1: Spin-coat PEDOT:PSS on an ITO substrate at 3000 rps for 40 seconds, followed by heating at 130 °C for 20 minutes.
[0110] Step 2: Spin coating 80 μL of PF8Cz at 3000 rps for 30 seconds, followed by annealing at 130 °C for 20 minutes;
[0111] Step 3: spin coating the quantum dots QDs-1 (18 mg / mL) synthesized in Example 1 at a speed of 3000 rps for 30 seconds, followed by annealing at 80° C. for 5 minutes;
[0112] Step 4: Spin coating ZnMgO (20 mg / mL) at 3000 rps for 30 seconds, followed by heating at 80 °C for 1 hour;
[0113] Step 5: Vacuum 5×10 -4 Pa, evaporate Al at a rate of 2 to 5 angstroms / second until the thickness reaches 1000 angstroms, and the evaporation is completed.
[0114] The device was encapsulated with epoxy resin and cover glass to obtain QLED-1.
[0115] In the same way, in the above step 3, the quantum dots QDs-2 (18 mg / mL) synthesized in comparative example 1 were spin-coated, and the other methods were the same to prepare QLED-2.
[0116] QLED-1 and QLED-2 were powered on and tested. The test data are shown in Table 1 below.
[0117] Table 1
[0118] type <![CDATA[V turn-on ]]> J(mA / cm2)@4V <![CDATA[CE max (cd / A)]]> <![CDATA[EQE max (%)]]> <![CDATA[L(cd / m 2 )@4V]]> PL(nm) QLED-1 2.4 174 85.6 19.2 138300 534 QLED-2 2.4 248 79.5 18.5 95570 532
[0119] It can be seen that the maximum current efficiency, maximum external quantum efficiency and brightness of the G-QLED device prepared using the green quantum dots of Example 1 are significantly improved, especially the brightness, which is increased from 95570 cd / m 2 Increased to 138300cd / m 2 , the optical performance of the device is greatly improved.
[0120] As attached Figure 1The EQE data of the QLED-1 device and the QLED-2 device shown in the figure show that the EQE of the G-QLED device prepared using the green light quantum dots of Example 1 reaches a maximum of 19.2% at a brightness of 50,000 hits, and the EQE remains stable as the brightness increases. However, the EQE of the G-QLED device prepared using the green light quantum dots of Comparative Example 1 reaches a maximum of 18.5% only at a brightness of about 25,000 nits, and gradually decreases with increasing brightness. At a brightness of 95,570 nits, the EQE is less than 10%. This shows that the CdZnSe core-shell quantum dots prepared by the method of the present invention have high luminous efficiency.
[0121] The stability and life test results of QLED-1 and QLED-2 devices constructed by QDs-1 and QDs-2 are shown in the attached figure. Figure 2 In constant current mode with an initial brightness of 10000nits, the device life calculation formula is:
[0122] LOn×T 50 =constant (where L0 is the initial brightness and n is the acceleration factor).
[0123] Acceleration factor n = 1.8, when the initial brightness is 10000 nits, the T of QLED-1 device and QLED-2 device 95 The lifespans are 2.16h and 0.038h respectively, T 50 The device lifespans are 30.4h and 1.27h respectively. When the initial brightness is converted to 1000nits, the T 95 The device lifespans are 136 hours and 2.4 hours respectively. It can be seen that the green light CdZnSe core-shell quantum dots synthesized by the preparation method of the present invention greatly improve the working life of the green light QLED device.
[0124] Although the present invention has disclosed multiple aspects and embodiments, other aspects and embodiments will be obvious to those skilled in the art, and several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The multiple aspects and embodiments disclosed in the present invention are only for illustration and are not intended to limit the present invention. The actual protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing core-shell quantum dots, characterized in that: The preparation method comprises the steps of: S1. providing a reaction system containing quantum dot nuclei; S2. Gradually increase the temperature of the reaction system of step S1, and simultaneously add a first selenium precursor, and after the temperature stabilizes, add a zinc precursor and a second selenium precursor to grow a ZnSe shell coating the quantum dot core, wherein the activity of the first selenium precursor is higher than that of the second selenium precursor, and the molar ratio of the first selenium precursor to the second selenium precursor is (1-3):
2.
2. The method for preparing core-shell quantum dots according to claim 1, characterized in that: The preparation method further comprises the steps of: S3, preparing a ZnSeS shell layer covering the ZnSe shell layer; S4, adding a first sulfur precursor to the reaction system of step S3 for reaction, cooling the temperature, and then adding a second sulfur precursor to grow a ZnS shell layer outside the ZnSeS shell layer, wherein the molar ratio of the first sulfur precursor to the second sulfur precursor is (10-15): (1-5).
3. The method for preparing core-shell quantum dots according to claim 1, characterized in that: In the step S2, the first selenium precursor is selected from one of octadecene-selenium and selenium powder-octadecene suspension, and the second selenium precursor is selected from at least one of diphenylphosphine selenium, triphenylphosphine selenium, tributylphosphine selenium and tripentylphosphine selenium; Preferably, the zinc precursor is selected from zinc carboxylates with a carbon chain length of 8 to 22; Preferably, the zinc precursor and the second selenium precursor are added to the reaction system in a dropwise manner; Preferably, the zinc precursor is added dropwise first, and then the second selenium precursor is added dropwise; Preferably, the dropping speed of the zinc precursor is 1-3 ml / min; Preferably, the dropping speed of the second selenium precursor is 3-8 ml / h.
4. The method for preparing core-shell quantum dots according to claim 1, characterized in that: In step S2, the temperature gradient is increased by 30° C. within 5-10 min; Preferably, the reaction time of the reaction system in step S2 is 15-40 min.
5. The method for preparing core-shell quantum dots according to claim 1, characterized in that: In the step S1, under the protection of an inert gas, a cadmium source and a zinc source are mixed and heated to a first temperature for reaction, the temperature is raised to a second temperature, and the first selenium precursor is added for reaction to obtain a reaction system containing CdZnSe cores; Preferably, the first temperature is 110°C-150°C, and the reaction time is 10-30 minutes; Preferably, the second temperature is 280° C., and the second temperature is maintained for 10-30 minutes; Preferably, the speed of adding the first selenium precursor is 1 ml / s, and the reaction time of adding the first selenium precursor is 1-5 min.
6. The method for preparing core-shell quantum dots according to claim 5, characterized in that: The reaction system containing CdZnSe cores further comprises a fatty amine ligand, and the volume ratio of the fatty amine ligand to the second selenium precursor is (1-3):
5.
7. The method for preparing core-shell quantum dots according to claim 2, characterized in that: In the step S4, the first sulfur precursor is selected from at least one of diphenylphosphine sulfide, triphenylphosphine sulfide, tributylphosphine sulfide, and tripentylphosphine sulfide, and the second sulfur precursor is selected from octadecene-thiol; Preferably, the first sulfur precursor is added to the reaction system in a dropwise manner; Preferably, the dropping speed of the first sulfur precursor is 5-15 ml / h; Preferably, the second sulfur precursor is added after the first sulfur precursor is added and reacted for 10-30 minutes.
8. The method for preparing core-shell quantum dots according to claim 2, wherein: In the step S4, the temperature is lowered to 200-250° C., and the second sulfur precursor is added; Preferably, after adding the second sulfur precursor and reacting for 5-15 minutes, the temperature drops to 20-25°C.
9. A core-shell quantum dot, characterized in that Stated otherwise, the core-shell quantum dots are obtained by the preparation method described in any one of claims 1-8.
10. A display device, characterized in that: The display device comprises the core-shell quantum dots as claimed in claim 9.
Citation Information
Patent Citations
Preparation method for nanocrystal with core-shell structure
CN109423274A
Core-shell quantum dot and preparation method thereof, and electronic device
CN111218284A
Blue-light indium phosphide quantum dot, preparation method thereof, electroluminescent device and display device
CN113956879A
Quantum dot, quantum dot composition, light emitting diode and display device
CN116656338A